About folklore in the creative activity of Mykhailo Starytsky and Mykola Lysenko and its influence on the formation of the Ukrainian professional music and drama theater - Kokhan, Liudmyla; Kokhan, Larysa (Creativity Studies, 2024)
The article is devoted to the study of folklore activities of Ukrainian playwright, writer, poet, translator, theatrical and cultural figure, director, philanthropist, director of the first Ukrainian professional theater, the so-called “theater of luminaries”, Mykhailo Starytsky (1840–1904) and the founder of the Ukrainian national opera, composer, pianist, conductor, folklorist, public figure Mykola Lysenko (1842–1912). The main attention is paid to the analysis of the playwright’s use of descriptions of rituals, customs, traditions, folk morals of Ukrainians, as well as examples of the use of small folk genres, phraseology. It was found that for the Ukrainian community the study and preservation of folk traditions in the second half of the 19th century played an important role in the formation of national self-identification and national consciousness. The origins, features and functions of ethnography in Starytsky’s works are determined, in particular it is proved that the playwright’s use of descriptions of Christian and pre-Christian rites was primarily aimed at a true image of traditional Ukrainian society, an important component of which were ancient rituals, games, music and drama actions. It is shown how the rites of the winter and summer cycles of the folk calendar are reflected in various ways in the artist’s work, which is the most saturated with various bright rituals and customs. It is proved that the study of folk music significantly influenced the composer’s creativity. It is confirmed, that folklore in the works of Starytsky and Lysenko had a positive effect on the formation of the Ukrainian professional theater as a music and drama one.